American carrier air power at the dawn of a new century - Lambeth, Benjamin S. (Santa Monica, CA : RAND, National Defense Research Institute, 2005)
The terrorist attacks against the United States on September 11, 2001, heralded the start of a fundamentally new era for American carrier-based air power. The ensuing war in Afghanistan required a deep-strike capability in the remotest part of Southwest Asia where the United States maintained virtually no regional access. In that war, U.S. carrier-based fighters substituted almost entirely for land-based theater air forces because of an absence of suitable forward operating locations for the latter. Barely more than a year later, the Navy's carriers again played a key role in conducting around-the-clock operations against Saddam Hussein's forces in Iraq. Six of 12 carriers and their air wings were surged to contribute to the campaign, with a seventh carrier battle group held in reserve in the Western Pacific and an eighth also deployed at sea and available for tasking. As borne out by those experiences, American carrier air power now operates as a massed force able to conduct coordinated deep-strike missions well beyond coastal reaches when aided by nonorganic tanking. The Navy's performance over Afghanistan and Iraq further showed how far the nation's carrier force has advanced since the end of the cold war in providing around-the-clock target coverage, consistently accurate target attack, and-for the first time in its history-multiple successful target attacks per sortie. A new Fleet Response Plan validated during Operation Iraqi Freedom promises to nearly double the number of carriers that can be surged and made ready for tasking on short notice. By the time U.S. naval aviation celebrates its 100th anniversary in 2011, it will have gained even greater combat leverage with the introduction of a new carrier-based stealth fighter and an ever-tighter fusion of sensors, information networks, and weapons.
Introduction -- Carrier air over Afghanistan -- Operation Iraqi freedom -- A new carrier operating concept -- The next-generation carrier -- The changing face of American carrier air power -- Conclusions.
Includes bibliographical references.
English.
Print version record.
Keywords: United States. -- Navy -- Aviation; United States. -- Marine Corps -- Aviation; 2001-2011; Aircraft carriers -- United States; Afghan War, 2001-2021 -- Aerial operations, American; War on Terrorism, 2001-2009.